Exploring the Experiences of Women Entrepreneurs in Pagadian City - Tan-awon, Grizzel Kate; Baldado, Laurence E.; Santillan, Joseph Angelo Maio P.; Sumicad Jr., Eligen H.; Batingal, Ace Virgel T. (Future Science / FSH-PH Publications, 2025)
This study explores the experiences of women entrepreneurs in Pagadian City, focusing on their challenges, motivations, and achievements. Women entrepreneurs play a vital role in the local economy, yet they often face unique struggles that require perseverance and innovation. Through interviews and observations, this research examines their personal and professional journeys, shedding light on the factors that influence their entrepreneurial ventures. The findings reveal that women entrepreneurs in Pagadian City encounter various challenges, including financial limitations, intense market competition, and societal expectations regarding gender roles. Despite these obstacles, many have demonstrated resilience and adaptability, utilizing innovative strategies to grow their businesses. Support systems, such as family, community networks, and local organizations, play a significant role in their success. This study also uncovers the motivations that drive these women to pursue entrepreneurship, such as achieving financial independence, fulfilling personal aspirations, and providing for their families. Their stories reflect the importance of empowerment, determination, and creativity in overcoming barriers and building sustainable enterprises. The insights from this research aim to inspire aspiring women entrepreneurs and encourage policymakers and organizations to create initiatives that address the needs of women-owned businesses. By fostering a supportive environment, these efforts can contribute to the growth of the local economy and promote gender equality in entrepreneurship.